Peran Lifestyle sebagai Pemoderasi antara Financial Literacy dan Self Control terhadap Penggunaan Paylater pada Mahasiswa Generasi Z - Lulu Novita Sari; Mardi Mardi; Khansha Sindra Irfani (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The surge in paylater service adoption among Generation Z has raised critical concerns regarding impulsive digital credit management. This study aims to analyze the influence of financial literacy and self-control on the intensity of paylater usage, incorporating lifestyle as a moderating variable among the 2022 cohort of students at the Faculty of Economics and Business, Universitas Negeri Jakarta. Utilizing a quantitative survey design, data were collected from 259 respondents selected through proportional random sampling and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results demonstrate that financial literacy has a significant positive impact on paylater usage, whereas self-control exhibits a significant negative influence. Regarding the moderating role of lifestyle, it was found to strengthen the effect of self-control on paylater usage, although it did not significantly moderate the relationship between financial literacy and such usage. These findings highlight the urgency of financial education and self-regulation in fostering prudent digital consumption patterns. This study provides valuable insights for educational institutions to strengthen financial management curricula, enabling students to engage with digital credit platforms more responsibly in the future